Effect of Plant Growth Regulators on Callus Induction in Piper betle L. var. Nigra: Pengaruh Berbagai Jenis ZPT terhadap Induksi Kalus Piper betle L. var. Nigra - Junairiah Junairiah; Ni'matuzahroh Ni'matuzahroh; Nabilah Istighfari Zuraidassanaaz; Lilis Sulistyorini (Journal Pharmasci (Journal of Pharmacy and Science), 2023)
Callus culture is one of the plant tissue culture techniques that used to study aspects of plant nutrition, somatic embryogenesis, cell suspension culture, secondary metabolite production, and genetic transformation. Callus induction was carried by adding growth regulators. Black betel (Piper betle L. var. nigra) is a medicinal plant that has the potential to produce secondary metabolites. The aim of this study was to obtain the best formula for callus induction of P. betle L. var. nigra. The single growth regulator used is 2,4-Dichlorophenoxyacetic acid (2,4-D), Benzyl Amino Purine (BAP), Indole Butyric Acid (IBA), Indole Acetic Acid (IAA), and Naphthalene Acetic Acid (NAA) with variations the concentration used is 0; 0.5; 1; 1.5; 2; 2.5 mg/L. Each treatment consisted of 6 replicates grown using Murashige and Skoog (MS) medium in vitro for eight weeks. The results showed that the 1.5 mg/L 2,4-D treatment produced the highest fresh weight (1389.5 mg) and dry weight (55.7 mg). Callus P. betle L. var. Nigra in various treatments showed various textures such as compact and friable with callus colors such as white, greenish-white, brownish-white, yellowish-green, greenish-yellow, brownish-yellow, greenish-brown, brown, and gray.